Synthesis, characterization, DFT calculations and anticancer activity of a new oxidovanadium(iv) complex with a ligand derived from o-vanillin and thiophene. (10th July 2019) - Rodríguez, María R.; Balsa, Lucía M.; Del Plá, Julián; García-Tojal, Javier; Pis-Diez, Reinaldo; Parajón-Costa, Beatriz S.; León, Ignacio E.; González-Baró, Ana C.
Abstract : New vanadium complex was synthesized and fully characterized showing promising anticancer activity on triple negative breast cancer cells. Abstract : From the interaction of the vanadyl ion with a ligand (HL), obtained by the condensation reaction of o -vanillin and 2-thiophenemethylamine, an oxidovanadium(iv ) complex (VOL2 ) was obtained. It was characterized by spectroscopic techniques, including solid state FTIR, Raman, EPR and diffuse reflectance, and UV-vis and EPR, in solution. Its thermal behavior was analyzed by means of TGA and DTA. Theoretical studies based on DFT computational methods aided in the interpretation and assignment of spectroscopic data. Cytotoxicity assays (48 h) against bone cancer cells (MG-63, IC50 = 50.4 ± 8.7), breast cancer cells (MCF-7, IC50 = 42.3 ± 4.7), (MDA-MB-231, IC50 = 29.0 ± 1.7) and a normal fibroblast (L929, IC50 = 71.0 ± 3.5) demonstrated the enhancement of the effectiveness and selectivity of the complex as compared with both the ligand and the free metal ion. Besides, the compound inhibits cell migration, increases ROS levels and facilitates apoptosis. On a whole, these results show the main mechanisms of the deleterious effects of [VOL2 ] in a triple negative breast cancer cell line (MDA-MB-231), demonstrating that this complex is a promising therapeutic agent for this kind of breast cancer.